Hirschsprung's Disease - Review of Clinical Features, Diagnosis and Treatment - Tkaczyk, Rafał; Świątek, Gabriela; Tomczyk, Jakub; Sosnowska, Weronika; Tomkiewicz, Maria; Taracha, Kalina; Tomkiewicz, Maciej; Brzozowska, Aleksandra; Trusz, Kornelia; Wanat, Iwona (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Hirschsprung's disease, also known as congenital aganglionic megacolon, is a rare congenital disorder that affects the large intestine. Due to the absence of ganglion cells, the affected segment of the colon becomes narrow and unable to relax. The disease is present from birth but may not always be immediately apparent. In this paper, we will attempt to present the current state of knowledge regarding the diagnosis and treatment of Hirschsprung's disease, based on the analysis of literature available on the PubMed platform. Description of the state of knowledge: Hirschsprung's disease (HSCR), also known as congenital aganglionosis of the colon, involves abnormal migration, proliferation, and differentiation of neural crest cells, leading to the absence of autonomic nerve ganglia within the colon. HSCR is associated with mutations in several genes, with RET, GDNF, EDNRB and SOX10 being identified as the main causes of the disease. Mutations in the RET gene are associated with the hereditary form of Hirschsprung's disease. Symptoms of HSCR appear in newborns and may include bilious vomiting, diarrhea associated with enterocolitis, failure to pass meconium within the first 24 hours of life, impaired peristalsis, jaundice, feeding difficulties, and progressive abdominal distension. Summary: Diagnosis is typically made based on clinical presentation, imaging studies, and biopsy. Treatment usually involves surgery to remove the affected segment of the colon and reconnect the healthy portions. Although postoperative complications are relatively common, long-term studies suggest that the majority of children with Hirschsprung's disease function well in society.